Deaminase-Dead Mouse APOBEC3 Is an In Vivo Retroviral Restriction Factor - Stavrou, Spyridon (J Virol, 2018)
The apolipoprotein B editing complex 3 (APOBEC3) proteins are potent retroviral restriction factors that are under strong positive selection, both in terms of gene copy number and sequence diversity. A common feature of all the members of the APOBEC3 family is the presence of one or two cytidine deamination domains, essential for cytidine deamination of retroviral reverse transcripts as well as packaging into virions. Several studies have indicated that human and mouse APOBEC3 proteins restrict retrovirus infection via cytidine deaminase (CD)-dependent and -independent means. To understand the relative contribution of CD-independent restriction in vivo, we created strains of transgenic mice on an APOBEC3 knockout background that express a deaminase-dead mouse APOBEC3 due to point mutations in both CD domains (E73Q/E253Q). Here, we show that the CD-dead APOBEC3 can restrict murine retroviruses in vivo. Moreover, unlike the wild-type protein, the mutant APOBEC3 is not packaged into virions but acts only as a cell-intrinsic restriction factor that blocks reverse transcription by incoming viruses. Finally, we show that wild-type and CD-dead mouse APOBEC3 can bind to murine leukemia virus (MLV) reverse transcriptase. Our findings suggest that the mouse APOBEC3 cytidine deaminase activity is not required for retrovirus restriction. IMPORTANCE APOBEC3 proteins are important host cellular restriction factors essential for restricting retrovirus infection by causing mutations in the virus genome and by blocking reverse transcription. While both methods of restriction function in vitro, little is known about their role during in vivo infection. By developing transgenic mice with mutations in the cytidine deamination domains needed for enzymatic activity and interaction with viral RNA, we show that APOBEC3 proteins can still restrict in vivo infection by interacting with reverse transcriptase and blocking its activity. These studies demonstrate that APOBEC3 proteins have evolved multiple means for blocking retrovirus infection and that all of these means function in vivo.